PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP KEAKTIFAN BELAJAR MATEMATIKA PESERTA DIDIK - Rahmi Yuliana; Hartini Hartini; Zul Muhammad Hajj (STKIP Paris Barantai, 2023)
The aims of this study are 1) To find out whether the use of the Team Games Tournament (TGT) type of cooperative learning model has an effect on the mathematics learning activity of seventh grade students of MTsN 2 Kotabaru. 2) To find out how much influence the use of the TGT type of cooperative learning model is seen from the mathematics learning activity of class VII MTsN 2 Kotabaru. The method used in this research is an experimental quantitative research method. The sample in the experimental class amounted to 37 people and in the control class there were 37 people out of 110 people total population. Data were collected using research instruments in the form of learning implementation observation sheets and student learning activity observation sheets. The results of the study stated that the use of the TGT Cooperative Learning Model had an effect on the mathematics learning activity of students in grade VII MTsN 2 Kotabaru, with the magnitude of the effect of the TGT type cooperative learning model on learning activities. students by 13.1%.